2023
DOI: 10.7759/cureus.33962
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Disseminated Herpes Zoster With Polyneuropathy Following the Third Dose of the Pfizer-BioNTech Vaccine

Abstract: SARS-CoV-2 pandemic resulted in the fast development of new vaccines, which helped contain the pandemic, but some adverse events started to rise. Recently, post-administration of mRNA-based vaccines, varicella-zoster virus (VZV) reactivation was reported. We report a case of disseminated herpes zoster with polyneuropathy and cerebrospinal fluid (CSF) findings following the Pfizer-BioNTech vaccine. Our observation aims to increase clinicians' awareness of a possible relationship between herpes zoster reactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Whatever the mechanism, the trigger for VZV reactivation resulting in DHZ should be consistent among different types of COVID-19 vaccinations. Indeed, this and previous studies found that DHZ could occur after the protein subunit, mRNA-based [ 6 , 7 ], viral vector [ 8 ], and inactivated vaccinations [ 9 ]. In addition, DHZ cases secondary to natural infections with SARS-CoV-2 have been reported [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Whatever the mechanism, the trigger for VZV reactivation resulting in DHZ should be consistent among different types of COVID-19 vaccinations. Indeed, this and previous studies found that DHZ could occur after the protein subunit, mRNA-based [ 6 , 7 ], viral vector [ 8 ], and inactivated vaccinations [ 9 ]. In addition, DHZ cases secondary to natural infections with SARS-CoV-2 have been reported [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 57%
“…With the addition of two cases from this study, only six cases of DHZ following COVID-19 vaccinations have been reported in immunocompetent patients [ 6 , 7 , 8 , 9 ]. The major characteristics of these cases are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disseminated HZ was more likely to be reported in patients with recent COVID-19 vaccinations than in controls; however, this finding was not statistically significant. Several previous studies have reported that HZ was disseminated after COVID-19 vaccination, including inactivated vaccines, nonreplicating viral vectors, and mRNA vaccines, in patients older than 65 years of age or in immunocompromised hosts [ 47 51 ]. However, this study reported that only one patient with disseminated HZ after vaccination was immunocompromised, and only 28.6% of patients were older than 65 years of age.…”
Section: Discussionmentioning
confidence: 99%